The changing Brazil Current system between 23°S-31°S: vertical structure and mesoscale dynamics - Biló, Tiago Carrilho (2015)
We use hydrographic and direct velocity observations from two quasi-synoptic cruises in conjunction with a primitive equation linear instability model, to investigate the Brazil Current (BC) downstream change effect between 23°S-30°S on the temporal mixed instabilities properties. The quasi-synoptic data revealed that the BC is ∼400-500 m deep to the north of the so-called Santos Bifurcation (26°S-28°S) and extends down to 1000 m to the south of it. We estimated that the BC receives at least 7 Sv from the Santos Bifurcation, which drastically alters the BC\'s velocity vertical structure and meanders characteristics as it flows poleward. Based on direct velocity measurements, we computed the mixed-instability properties at three different latitudes (24°S, 26°S and 30°S). The instability analysis revealed unstable current systems to mesoscale perturbations with maximum growth rates of 0.12, 0.19 and 0.06 day-1 at 24°S, 26°S and 30°S respectively. The corresponding downstream phase speeds are -0.19, -0.24 and -0.26 m s-1. The analysis of the mean-to-eddy energy conversion terms show that the barotropic instability drains 60-90% less energy from the background state than the baroclinic instability. Nevertheless, the maximum growth rates are at least the double in magnitude when both instabilities occur simultaneously. The topography presents a stabilizing effect for both kind of instabilities along all the BC path. At the vicinities of the Cape Santa Marta (28°S), we explored the the recurrent cyclonic meanders of the BC. Combining a wide range of observations, we provided a overview of such features and the relations between its velocity patterns, the water properties (temperature, salinity, nutrients), chlorophyll-a distribution and the BC variability. The top-bottom quasi-synoptic velocity measurements depicted cyclonic meanders over the continental slope with diameters larger than 100 km and vertically extending to approximately 1500 m depth. Moreover, the observed eddies seems to trap and recirculate a small portion (∼1.5 to 4 Sv) of the BC main flow (-13.16 to -17.89 Sv), which is consisted of Tropical Water (TW), South Atlantic Central Water (SACW), Antarctic Intermediate Water (AAIW) and Upper Circumpolar Deep Water (UCDW). Additionally, we presented observational evidence that the meanders actively influence the transport of nutrient-rich shelf waters to the open ocean enhancing the primary productivity at the photic zone over the continental slope. Satellite imagery show that these cyclonic events occur 5-6 times per year and are generally associated with wave-like perturbations on the flow with mean wavelength of ∼219 km. Finally, Empirical Orthogonal Functions (EOF) analysis computed from an array of mooring lines show that more than half of the along-isobath velocity variance on the continental slope is explained by the BC mesoscale activity.